PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWANPADA KANTOR PUSAT PT. SARANA MULTI DAYA JAKARTA SELATAN - Mega Dwi Cahyani Mega Dwi Cahyani; Abdul Azis (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. The aim of this research is to determine the influence of work motivation and discipline on employee performance at the PT Sarana Multi Daya Head Office, South Jakarta, both partially and simultaneously. The method used is a quantitative method with a descriptive approach. The population was 44 people and the sample size was 44 people. Data collection techniques use observation, literature study, questionnaires, and documentation. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this research show that the value of multiple linear regression analysis obtained the regression equation Y = 1.575 + 0.152X1 + 0.815X2. The f test or simultaneous test shows the results of Fcount 36.469 > Ftable 3.230 and a significant value of 0.000 < 0.05. In the results of the coefficient of determination test, the R square result is 0.64.0 or 64%, which means it can be concluded that the variables Motivation (X1) and Work Discipline (X2) have an effect on the Employee Performance variable (Y). Keywords: Motivation and Work Discipline Employee Performance